2021
DOI: 10.1002/pmrj.12570
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative malnutrition is a risk factor for delayed recovery of mobilization after total hip arthroplasty

Abstract: Introduction: Many studies have examined nutritional status and deteriorated postoperative outcomes in patients undergoing total hip arthroplasty. However, few studies have focused on nutritional status and postoperative mobility. Objective: To investigate the impact of preoperative nutritional status on mobility after total hip arthroplasty. Design: Retrospective single-institution cohort study. Setting: Orthopedic inpatient rehabilitation center. Participants: A total of 503 patients who underwent unilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
(109 reference statements)
0
8
0
Order By: Relevance
“…Several factors lead to delayed physical function recovery. 37 Walking ability and muscle strength are closely related, 8 and we reported the importance of preoperative quadriceps strength for early walking independence in older patients undergoing THA. 9 Furthermore, balance skills, including one-leg standing time (OLST), are known as good indicators of walking ability and are important for evaluating lower limb ability.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Several factors lead to delayed physical function recovery. 37 Walking ability and muscle strength are closely related, 8 and we reported the importance of preoperative quadriceps strength for early walking independence in older patients undergoing THA. 9 Furthermore, balance skills, including one-leg standing time (OLST), are known as good indicators of walking ability and are important for evaluating lower limb ability.…”
Section: Introductionmentioning
confidence: 76%
“…According to the postoperative clinical pathway in our hospital, sutures were removed on the 10th postoperative day and patients were discharged home on the 11th day if they were walking and climbing stairs independently at this point, but if they needed assistance with these activities, they were transferred to a rehabilitation facility. 5,7…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding elective THA, Bala et al 13 queried the Medicare database from 2007 to 2016 and demonstrated a significant association between malnutrition and postoperative complications as well as significantly increased reimbursements in elective total joint arthroplasty. In addition, Nanri et al 28 reported that nutrition status assessed by the Controlling Nutritional Status (CONUT) score predicted delayed recovery of mobilization after THA. Furthermore, a recent meta‐analysis conducted by Tsantes et al 29 concluded that malnutrition is associated with the risk of surgical site and periprosthetic joint infections after total knee and hip arthroplasty 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need to explore these well-validated INSTs in the field of arthroplasty. Nanri et al [ 43 ] evaluated 503 patients undergoing primary total hip arthroplasty and found that 18.9% were classified as malnourished by CONUT. Our study further revealed that the percentage of PJI patients identified as malnourished by CONUT raised to 48.1%.…”
Section: Discussionmentioning
confidence: 99%